ChemInform Abstract: Novel Synthesis of 3‐Phenyl‐chromen‐4‐ones Using N‐Heterocylic Carbene as Organocatalyst: An Efficient Domino Catalysis Type Approach. Issue 40 (12th September 2013) - Mishra, Priya; Singh, Sarita; Ankit, Preyas; Fatma, Shahin; Singh, Divya; Singh, Jagdamba
Abstract An environmentally benign approach for the synthesis of isoflavones (III) by a simple and efficient organo‐catalyzed reaction of substituted phenacyl bromides and salicylaldehydes is given.